Extent of computerization of state college and university libraries in the Philippines - Salvador, Virginia P. 1964-; Cruz, Ma. Divina P.; Esquejo, Nemesio A. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1998)
Information is generated left and right and it is the responsibility of the libraries to provide the right information to the right person at the right time. With information explosion, how can libraries be able to provide access to information more effectively and efficiently? State colleges and universities (SCU) are addressing this problem through the use of computer technology. It is towards this end that this research is carried out. This study is an investigation on which libraries of state colleges and universities in the Philippines are already computerizing their operations.
Of the 108 state colleges and university libraries which were sent questionnaires, 83(76.9) responded. Of this number, 27(32.5) SCU libraries use computers in their library operations. Most of these libraries are still in their initial stage of computerization. The respondents stated that their goals and objectives are for automation. Their management also have a positive attitude to automation and have allocated financial resources as well towards this end. Since these colleges and universities are based on state charter, government allocation is the main source of funds although part of the funding also comes from benefactors and donor institutions.
Fifty-six of the respondents (51.9) are not yet computerized but 18 (32.1) of them expect to utilize computers in a span of 3-5 years. Sixteen (28.6) expected to automate within 1-2 years. An increasing demand to access information was the main reason for computerization. Acquisitions, cataloging and circulation were the library processes they wanted to computerize but was not able due to unavailability of funds and technical personnel. Overall, it can be said that computerization of SCU libraries in the country is still in its infancy stage. This further substantiate Pellazar'ss (1996) study which found that although most of the libraries are not yet computerized, the respondents have shown their desire to computerize their library operations.
Computer print-out (photocopy)
Vita.
Special Problem (Master of Library Science)
Keywords: Academic libraries -- Philippines -- Automation; Libraries -- Philippines -- Automation